2022
DOI: 10.21203/rs.3.rs-1911822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of postoperative radiotherapy in patients with vulvar squamous carcinoma: findings based on the SEER database

Abstract: Introduction: The role of postoperative radiotherapy in treating squamous cell carcinoma of the vulva remains controversial. This study evaluated the effect of radiotherapy on the survival of patients with postoperative squamous cell carcinoma of the vulva.Methods: Clinical and prognostic information on patients diagnosed with vulvar squamous cell carcinoma from 2010 to 2015 was collected from the Surveillance, Epidemiology, and Prognosis (SEER) database. A propensity score matching (PSM) approach was used to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For the management of dysphagia and pain, palliative radiotherapy utilizing intracavitary brachytherapy or external beam radiotherapy is effective. Li et al found that postoperative radiotherapy improves survival outcomes for patients with AJCC stages III, N1, a large tumor diameter, and lymph node metastases (33), based on a database-based retrospective study of 3,571 patients with vulvar squamous cell carcinoma. In this study, the P > 0.1 for the chemotherapy group may be due to the lack of clarity in the de nition of the nonchemotherapy group (none/unknown) in the database.…”
Section: Surgery Radiotherapy Chemotherapymentioning
confidence: 99%
“…For the management of dysphagia and pain, palliative radiotherapy utilizing intracavitary brachytherapy or external beam radiotherapy is effective. Li et al found that postoperative radiotherapy improves survival outcomes for patients with AJCC stages III, N1, a large tumor diameter, and lymph node metastases (33), based on a database-based retrospective study of 3,571 patients with vulvar squamous cell carcinoma. In this study, the P > 0.1 for the chemotherapy group may be due to the lack of clarity in the de nition of the nonchemotherapy group (none/unknown) in the database.…”
Section: Surgery Radiotherapy Chemotherapymentioning
confidence: 99%